USULAN MENGURANGI WAKTU SET UP WIND UP MESIN ABC-1 DENGAN METODE SMED - Puspita Sary, Indri; Gunawan, Fandy; Widodo, Kukuh (Jurnal Sains Ilmu Teknologi Industri, 2022)
Bias cutting process is a process of cutting treatment into ply, breaker, chaffer, and flipper. However, in the production of breaker production targets are often not achieved. Field observations made on the ABC-1 machine that produces breakers show that the setup time in the win up process is quite long and can be reduced so that the production process time increases. To reduce setup time, wind up modifications, design and construction of empty storage liners were carried out and the application of the SMED method in the setup process. The total setup time for changing the empty liner and filling the previous empty storage liner is 378.62 seconds. After modifying the wind up, designing an empty storage liner and applying the SMED method to the setup process, the setup time decreased to 262 seconds or 30.8% decrease from the previous time.